Exploring the effects of Pair-Interaction Model on improving Indonesian adult learners’ English proficiency - Abdul Hakim Yassi; Waode Hanafiah; Harlinah Sahib; Muhammad Aswad; Nur Fadillah Nurchalis; Zeinab Azizi (Universitas Syiah Kuala, 2023)
The phenomenon of poor English language proficiency among Indonesian students suggests revisiting the instructional methods that have long been commonly used in English as a foreign language (EFL) classrooms. This long-lasting problem makes it essential for English practitioners to seek alternative approaches paving the ground for the EFL learners to reach more promising achievements. One of the approaches that may fill in this lacuna is Pair-Interaction Model (PIM). Therefore, the present study was an attempt to disclose the effects of PIM on fostering Indonesian EFL learners’ proficiency compared to the Grammar-Translation Method (GTM). For this purpose, a total of 90 first-year English students from three renowned universities in South Sulawesi, i.e. Hasanuddin University, Indonesian Moslem University situated in Makassar, and the Muhammadiyah University of Pare-Pare, were selected using a purposive sampling technique. The participants went through a pre-test, an intervention, and a post-test procedures. Findings revealed that the English proficiency of the participants who received instructions based on the principles and procedures of PIM significantly improved at the end of the interventions. This improvement was particularly seen in the participants’ grammar knowledge and speaking skills. The findings offered strong evidence that PIM can be implemented in the Indonesian classes to foster EFL learners’ proficiency. The study concludes by offering some implications for relevant stakeholders and opening up some avenues for further research.